An exceedingly rare localization of a brown tumor in a hemodialysis patient. Issue 4 (6th December 2012) - Karagoz, Ali; Turkmen, Kultigin; Yazici, Raziye; Arslan, Sevket; Baktık, Suleyman; Karanis, Meryem Ilkay Eren; Altintepe, Lutfullah; Guney, Ibrahim
Abstract: Brown tumor, which is seen in the context of hyperparathyroidism, is defined as a uremic bone disease characterized by increased osteoclastic activity and fibroblastic proliferation in the involved bone. In chronic renal failure, there is an excessive parathyroid hormone secretion due to hypocalcemia, hyperphosphatemia, and vitamin D deficiency. Brown tumor of the femur, facial bones, mandible, sternum, ribs, and pelvis are rare, whereas, it rarely involves sacrum. Here, we presented a brown tumor of the sacrum that developed secondary to parathyroid hyperplasia in a patient receiving hemodialysis.